Selected Trace Elements in Egyptian Females with Preeclampsia - Abdelrahman Emam; Attia Attia (International Journal of Medical Arts, 2020)
Background: Evidence exist indicating that, trace elements could play a role in preeclampsia (PE). However, controversy exist regarding the role of the value of trace elements supplementation on the pregnancy outcome. Aim of the work: To estimate serum levels of some trace elements (selenium, calcium, magnesium, iron and zinc) in females developed preeclampsia and compare them to healthy pregnant females and correlate it with pregnancy outcome.Patients and Methods: 140 females were included in each group (preeclampsia and controls). All had been assessed clinically, and by laboratory and ultrasound investigations. In addition, serum levels of selenium, calcium, magnesium, iron and zinc, had been determined and correlated with pregnancy outcome. Results: There was statistically significant increase of all trace elements in preeclamptic when compared to control groups. There was significant increase of females with deficient zinc, iron, calcium, magnesium and selenium in PE when compared to control group (83.6%, 19.3%, 30.7%, 27.9% and 40.0% vs 22.9%, 5.7%, 4.3%, 2.9% and 5.0% respectively). The odds ratio where higher for zinc, followed by selenium, magnesium, calcium and finally iron deficiency. In addition, zinc, iron, calcium, magnesium and selenium were inversely and significantly correlated with systolic blood pressure. Preeclampsia was associated with worse maternal-fetal outcome when compared to controls. Conclusion: Lower levels of studied trace elements are associated with development of preeclampsia and we assume that, supplementation by such elements could reduce the risk of preeclampsia. However, this assumption needs to confirmed in future trials.